Program Online Learning Sebagai Faktor Penunjang Keunggulan Kompetitif Binus University - Kerta, Johan Muliadi; Andrian, Ronny (Bina Nusantara University, 2011)
Online learning has become a way to improve efficiency in the learning process without reducing the quality of learning itself. Colleges that run it hope that the program becomes an attraction for prospective students, especially those with limitation to follow the regular program. The goal of this research was to find out whether Binus Online Learning Program has any influence to the competitive advantage of Binus University. Data were compiled by distributing questionnaires to 100 respondents consist of the students and lecturers on Binus Online Learning Program. This thesis is based on a quantitative methodology to gather and analyze the data to find out if they were any correlation between Online Learning Program and the competitive advantage of Binus University. It can be concluded that there are some positive and significant influences of Online Learning Program to the competitive advantage of Binus University. Therefore, promoting and developing Online Learning Program will increase the competitive advantage of Binus University, and cover the target market which regular programs do not.